2021
DOI: 10.1177/0886260521997454
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Risk for Increased Intimate Partner Violence Among Gay, Bisexual and Other Men Who Have Sex With Men in the United States

Abstract: Stay at home orders–intended to reduce the spread of COVID-19 by limiting social contact–have forced people to remain in their homes. The additional stressors created by the need to stay home and socially isolate may act as triggers to intimate partner violence (IPV). In this article, we present data from a recent online cross-sectional survey with gay, bisexual and other men who have sex with men (GBMSM) in the United States to illustrate changes in IPV risks that have occurred during the U.S. COVID-19 epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 25 publications
2
48
2
Order By: Relevance
“…Barbara and colleagues showed a reduction in the number of women seeking help at the Service for Sexual and Domestic Violence during home confinement [ 75 ]. Accordingly, other studies found a reduction in reporting DV and seeking help during lockdown [ 53 , 76 79 ]. Conversely, two studies reported an increase in the rate of calls to help lines for DV [ 80 , 81 ], and the successful use of telemedicine in preventing and detecting violence cases [ 81 ].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Barbara and colleagues showed a reduction in the number of women seeking help at the Service for Sexual and Domestic Violence during home confinement [ 75 ]. Accordingly, other studies found a reduction in reporting DV and seeking help during lockdown [ 53 , 76 79 ]. Conversely, two studies reported an increase in the rate of calls to help lines for DV [ 80 , 81 ], and the successful use of telemedicine in preventing and detecting violence cases [ 81 ].…”
Section: Resultsmentioning
confidence: 90%
“…For what concerns the effects of COVID-19 on IPV, literature revealed increased levels of both hetero and self-directed violence [ 50 , 51 , 53 55 ], while report rates and supporting network seeking were found to decrease during the pandemic [ 53 , 75 79 ]. Mitigation measures highlighted the need for improvement of support services for IPV victims.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One study linked PrEP discontinuation during COVID-19 to overall reductions in casual sex, finding that 86% of participants attributed their discontinuation to a decreased number of casual sexual encounters ( Hammoud et al, 2020a ). Efforts to encourage social distancing during the COVID-19 pandemic may also be redefining SGM relationships with sexual health services; some studies have reported reductions in access to sexual healthcare services including HIV testing, PrEP services, and other reproductive services ( Nagendra et al, 2020 , Stephenson et al, 2021a , Stephenson et al, 2021b ) ( Sanchez et al, 2020a , Sanchez et al, 2020b , Stephenson et al, 2021a , Stephenson et al, 2021b ).…”
Section: Prep Use and Other Sexual Health Services During The Covid-19 Pandemicmentioning
confidence: 99%
“…During the COVID-19 pandemic some have suggested that social confinement may impact experience of IPV and access to IPV resources during the pandemic ( Phillips et al, 2020 , Tomar et al, 2021 ). Some surveillance data has suggested increases in domestic violence service-seeking during the COVID-19 pandemic in general populations ( Pedrosa et al, 2020 ) and one study found increased experience of IPV among adult gay and bisexual men in the first three months of COVID-19 lockdown ( Stephenson et al, 2021a , Stephenson et al, 2021b ); however, no known studies have examined the impact of COVID-19 related social distancing and IPV in SGM young adult populations.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…73 Finally, being forced to stay at home made LGBTIQ individuals to be more exposed to the risk of social isolation and lack of dating interaction, with a drastic decrease of regular sexual and relational activities and an increased risk of sexual and relational activities under the effect of illicit substances, 74 and sexual and intimate partner violence. 75 Therefore, the COVID-19 pandemic led to a long-lasting exposure to adverse circumstances among LGBTQI individuals in Portugal and Brazil.…”
Section: Lgbtiq Topicsmentioning
confidence: 99%